2014
DOI: 10.1186/2193-1801-3-652
|View full text |Cite
|
Sign up to set email alerts
|

Change of the age and performance of swimmers across World Championships and Olympic Games finals from 1992 to 2013 – a cross-sectional data analysis

Abstract: The aims of the present study were to investigate the changes in the age and in swimming performance of finalists in World Championships (1994–2013) and Olympic Games (1992–2012) competing in all events/races (stroke and distance). Data of 3,295 performances from 1,615 women and 1,680 men were analysed using correlation analyses and magnitudes of effect sizes. In the World Championships, the age of the finalists increased for all strokes and distances with exception of 200 m backstroke in women, and 400 m free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
4
32
1
2
Order By: Relevance
“…The present study includes swim performances of multiple generations, necessitating the correction of evolution in a given sport . The continuous increase in world‐class performances at Olympic Games and World Championships clearly reflects the evolution in a sport, as well as the improvement of world records . For example, at the 100 m freestyle event, the world record for females has been improved from 54.48 seconds to 51.71 seconds with 2.9 seconds (~5.3%) from 1994 to 2017 and for males from 48.42 seconds to 47.04 seconds (fastest time in textile) with 1.38 seconds (~2.9%).…”
Section: Methodsmentioning
confidence: 99%
“…The present study includes swim performances of multiple generations, necessitating the correction of evolution in a given sport . The continuous increase in world‐class performances at Olympic Games and World Championships clearly reflects the evolution in a sport, as well as the improvement of world records . For example, at the 100 m freestyle event, the world record for females has been improved from 54.48 seconds to 51.71 seconds with 2.9 seconds (~5.3%) from 1994 to 2017 and for males from 48.42 seconds to 47.04 seconds (fastest time in textile) with 1.38 seconds (~2.9%).…”
Section: Methodsmentioning
confidence: 99%
“…A potential explanation for the findings for the unchanged participation in younger age groups (<40 years) could be the fact that the fastest freestyle swimmers in younger age groups still compete at world-class level races such as the World Championships and the Olympic Games (Allen et al 2014;Allen and Hopkins 2015;König et al 2014). However, also, other reasons might explain this trend.…”
Section: Participation Increased In Women and Menmentioning
confidence: 99%
“…Improvements in freestyle swimming performance in elite swimmers competing at a world-class level (e.g., World Championships, Olympic Games) are well investigated (König et al 2014;Nevill et al 2007;O'Connor and Vozenilek 2011;Stanula et al 2012). Nevill et al (2007) analyzed swimming speeds in 100-, 200-, and 400-m freestyle world record times since 1957 for men and women and found that swimming speeds showed a period of Baccelerated improvement^during the 1960-1970 period, but were plateauing after 1970.…”
Section: Introductionmentioning
confidence: 99%
“…Athletic performance increases from birth to youth reaching at peak levels at some points in early adulthood and declines thereafter (Moore 1975;Tanaka and Seals 1997;Berthelot et al 2012). The age at which peak performance is achieved is different depending upon sports disciplines and is typically in the range of 20-30 years old (Schulz and Curnow 1988;Allen et al 2014;Konig et al 2014). Average ages of peak performance for swimming are younger than those of running (Berthelot et al 2012).…”
Section: Introductionmentioning
confidence: 96%